Analysis of Solar Panel Design as a Power Source For CCTV at PT. Link NET, TBK - Asrul Andi; Zuraidah Tharo; Dicky Lesmana (Jurnal Scientia, 2024)
A computer system that uses a video camera to display and record an image at the time and place where the device is installed is CCTV. However, CCTV currently relies on PLN sources. If the PLN source goes out, CCTV will not work. One solution to overcome PLN sources that often go out is to use solar energy and remember that solar energy is very environmentally friendly. This CCTV uses an Arduino Nano microcontroller as a monitoring of battery voltage as a source of electrical power assisted by SCC to regulate the incoming current from the solar panel and the output current to the load used and the battery as a storage voltage of one of the electronic devices that are often used by humans.